Construction of the electromagnetic mill with the grinding system, classification of crushed minerals and the control system. Issue 20 (2016) - Wołosiewicz-Głąb, Marta; Ogonowski, Szymon; Foszcz, Dariusz
Abstract: The article presents the construction of an innovative electromagnetic mill, which in comparison to traditional solutions provide a significant reduction of energy consumption and higher technological performance. The device is equipped with a control system, measuring grinding quality or analyzing the operating status of the mill. Direct control of the grinding process is implemented in industrial controllers (PLC) and is supported by the optimization algorithms that run in the supervisory control system (SCADA).